Immediate outcome of meconium aspiration syndrome with respect to neonatal maturity and birth weight - Ahmed, Nazeer; Bavalatti, Rajesh Ashok; Thobbi , Achyut N. (International Journal of Contemporary Pediatrics, 2023)
Background: About 13% of live births result in MSAF, and as gestational age at birth increases, this percentage increases as well. About 5% of babies born with MSAF develop MAS (meconium aspiration syndrome). The mortality rate from MAS is still as high as 3-5 percent, even with modern NICU care. Methods: This study was a hospital-based a prospective observational study over an 18-months period, and all babies were admitted to the NICU who satisfied the MAS criteria were added in the study. The babies were monitored for their immediate outcome. Results: MAS was more prevalent among mother who had a history of pregnancy-induced hypertension and in neonates who were in fetal distress. With a mean gestational age of 38-40 weeks and a mean birth weight of 2.76 kg, it is more common in term newborns and babies born by caesarean section. The most frequent cause of death, birth asphyxia, which accounted for 30.7% of cases of MAS, was most frequently associated with neonates who were depressed at birth. Conclusions: Term and post-term neonates with weight >2.5 kg at birth are frequently associated with MAS. When meconium was present below the vocal cords, a low APGAR score at 1 minute and thick meconium were associated with a higher mortality rate. Non-vigorous babies require early and effective management, and early assisted ventilator support may be necessary when there is evidence of thick meconium. Asphyxiated babies should be carefully monitored. effective intrapartum suctioning, neonatal care, an accurate diagnosis and prompt treatment can significantly lessen the complications, morbidity and mortality in meconium aspiration syndrome.